國民核心素養的課程發展意涵National Core Competencies and Its Implication to - 蔡清田 Ching-Tien Tsai; 陳延興 Yen-Hsin Chen (Higher Education Foundation, 2013)
「國民核心素養」不僅意指每一個「國民」都須具備的「核心素養」，也屬於 新興的課程研究理念，是一種有理論依據的理論構念，具有課程研究發展的研究價值。研究者曾主持《K-12中小學一貫課程綱要核心素養與各領域連貫體系研究》以及《K-12各教育階段核心素養與各領域課程統整研究》等整合型研究，本研究在此「國民核心素養」課程研究與相關著作的基礎之上，進一步探討「國民核心素養」的課程發展重要性與意涵，可做為我國實施「十二年國民基本教育」、「建置中小學課程連貫與統整」之配套子計畫及其具體方案如「建置十二年一貫課程體系方案」等課程改革之參考，甚至可做為未來研發《十二年一貫課程體系指引》與《十二年國民基本教育課程綱要》之「國民核心素養」的理論依據，既可做為提升我國國民的「核心素養」之實踐參考，更可做為建構我國「國民核心素養」之理論基礎。National core competencies not only are the necessary core competencies that everyone should have in Taiwan, but also are new curriculum theoretical constructs which have their theoretical rationale. The authors in this paper argue the importance of national core competencies and articulate the meaning of national core competencies. The authors of the article have done the researches on the "A Research of Core Competencies of K-12 Curriculum Guideline and Continuity in Different Learning Areas" and "A Study of Core Competencies in Different Schooling Stages and Curriculum Integration of Different Learning Areas" for the National Academy of Education Research. Based on these two researches, the authors in this paper further explores the importance of national core competencies and articulated meaning of national core competencies. In this paper, the authors also suggest that the national core competencies should be the key stone of curriculum reform of K-12 national foundation education, and thus could build a structure of curriculum system of national foundation education in Taiwan.